Beliefs-oriented subject-matter didactics: Design of a seminar and a book on calculus education - Dilling, Frederik; Stoffels, Gero; Witzke, Ingo (LUMAT: International Journal on Math, Science and Technology Education, 2024)
This paper presents a modified approach to subject-matter didactics, in which the focus is not on the content itself, but on the students’ view of the content. The introduction deals with an overview of subject-matter didactics and the notion of beliefs used in this paper. The main portion of the paper deals with presenting the concepts of a book and a seminar based on the student-centered subject-matter didactics approach. For the first qualitative evaluation, selected reflections of students are analyzed. Finally, initial findings are summarized and an outlook is provided.